(3GdWQKhf aj NHQ GdHQZhKs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3hHYO abO Cda MGaX GdYUQ CHh GdaVd GHf MLQ LRFkG SeGg GdHSW GdeHKhK ai NHQ GdHQZhK hgPG LRAG ajg EaGOI JMJhi Ydi Pdc hRjGOI jSei HGdWQKhK ai ahGFO GdHQZhK s
(3BNQgG (B:s
(3hRYehG Cf TMe GdKYdH EPG Wdi Hg ShOG hYhO hLYd ai EMOi RhGi GdHjJ aEf GdHQGZjK jLJeYf Ydjg GfJgi GdJCdja hJe hGddg CYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1110s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B(37 (3d(B) s
Keywords: (3GdMOjK h GdeUWdMs